Randomised study of ezetimibe, start doses of original statins, and their combination in patients with coronary heart disease and hyperlipidemia Part 2. Therapy effects on the levels of C-reactive protein and proinflammatory cytokines - A. V. Susekov; M. Yu. Zubareva; T. A. Rozhkova; V. P. Masenko (Кардиоваскулярная терапия и профилактика)
Aim. To assess the effects of original statins as monotherapy or in combination with ezetimibe on the levels of proinflammatory cytokines and high-sensitive C-reactive protein (hsCRP) in patients with coronary heart disease (CHD) and hyperlipidemia (HLP). Material and methods. The study included 60 male and female patients with CHD, primary polygenic HLP, and the levels of low-density lipoprotein cholesterol (LDL-CH) of 2,9-4,9 mmol/l. Monotherapy with original statins or ezetimibe lasted for 6 months, while the combination therapy lasted for 3 months. In all randomised patients, the levels of hsCRP, interleukin 6 (IL-6), and monocyte chemotactic protein-1 (MCP-1) were measured at baseline, 12 and 24 weeks after the therapy started. Results. At baseline, median hsCRP levels in the groups of Ezetrol, Zocor, Liprimar, and Crestor monotherapy were 0,5-0,88 mg/l, with no significant dynamics after 3 months of the treatment. Baseline IL-6 levels across the monotherapy groups were 1,94-2,54 pg/ml; at 3 months, there was a non-significant reduction by 7-32 %. After 3 months of the therapy, the decrease in MCP-1 levels was not statistically significant (-1,3-7,7 %). The combined therapy did not result in a significant dynamics of hsCRP concentrations, with the exception of the group receiving Ezetrol and Liprimar. Although the combined therapy further reduced MCP-1 levels (by 30-78 pg/ml), these changes were not statistically significant. No significant difference was observed across statin and Ezetrol groups in terms of their effects on IL-6 and MCP-1 levels. Conclusion. The comparison of the three treatment schemes demonstrated similar, but not statistically significant reduction on the levels of hsCRP, IL-6, and MCP-1. No marked benefits were observed for either monotherapy or combination therapy over 12-24 weeks of the follow-up.